TRP Channels as Sensors of Bacterial Endotoxins - Boonen, Brett (Toxins (Basel), 2018)
The cellular and systemic effects induced by bacterial lipopolysaccharides (LPS) have been solely attributed to the activation of the Toll-like receptor 4 (TLR4) signalling cascade. However, recent studies have shown that LPS activates several members of the Transient Receptor Potential (TRP) family of cation channels. Indeed, LPS induces activation of the broadly-tuned chemosensor TRPA1 in sensory neurons in a TLR4-independent manner, and genetic ablation of this channel reduced mouse pain and inflammatory responses triggered by LPS and the gustatory-mediated avoidance to LPS in fruit flies. LPS was also shown to activate TRPV4 channels in airway epithelial cells, an effect leading to an immediate production of bactericidal nitric oxide and to an increase in ciliary beat frequency. In this review, we discuss the role of TRP channels as sensors of bacterial endotoxins, and therefore, as crucial players in the timely detection of invading gram-negative bacteria.